Use of real-world data for decision making in Canada and United Kingdom - P. A. Mukhortova; P. V. Gorkavenko; Yu. V. Strunina; V. V. Omelyanovskiy; V. V. Kalinichenko (Реальная клиническая практика: данные и доказательства)
This article provides an overview of approaches to the use of real-world data (RWD) and real-world evidence (RWE) in the processes of registration and health technology assessment in Canada and the UK, as well as a brief description of tools for health management decision-making, the Canadian Real-world Evidence for Value in Cancer Collaboration and electronic databases and registries. Information is provided on when RWE submission is possible and recommended, and what requirements the regulatory agencies have for RWD and RWE.